2022
DOI: 10.1111/jocn.16479
|View full text |Cite
|
Sign up to set email alerts
|

The effect of educational interventions in managing nurses' alarm fatigue: An integrative review

Abstract: Background: Alarm fatigue is becoming more widely acknowledged as a serious safety concern in modern clinical practice. Nurses are not always proficient in the alarms' functions and capabilities, and they do not undertake training regularly. Educating nurses on alarms maintains their knowledge and abilities in complex clinical settings. Some education has been undertaken to improve clinical alarm response, but the evidence for evaluating the effectiveness of nurse education interventions is limited. Objective:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Asadi et al confirm this by reporting that the fatigue in nurses who were trained in working with ventilators and alarm settings was significantly lower [26]. According to the authors of the 2022 review, education may be key to minimising fatigue [10]. A 2019 project conducted in China revealed similar findings.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Asadi et al confirm this by reporting that the fatigue in nurses who were trained in working with ventilators and alarm settings was significantly lower [26]. According to the authors of the 2022 review, education may be key to minimising fatigue [10]. A 2019 project conducted in China revealed similar findings.…”
Section: Discussionmentioning
confidence: 90%
“…Fatigue caused by alarms is increasingly recognized as a serious problem related to patient safety in contemporary clinical practice [10]. The specificity of work in ICUs led critical care nurses to report low positive patient safety attitudes [11].…”
Section: Introductionmentioning
confidence: 99%
“…There are factors that may contribute to enhancing alarm fatigue among nurses and need to be investigated to provide future strategic plan to manage them. In a recent study that was conducted by Nyarko et al 2023, 13 factors such as years of experience in the critical care unit and having policies related to alarm management, type of intensive care units were associated with an increased risk of alarm fatigue. Another study has shown that appeared that nurses’ alarm fatigue was negatively correlated with their participation in ward monitoring device training programs and positively correlated with working 12-hour shifts (as opposed to 8-hour and 24-hour shifts) and working in Intensive Cardiac Surveillance Units (as opposed to other ICUs).…”
Section: Introductionmentioning
confidence: 96%
“… 6 False alarms may result in undesired actions such as ignoring or reducing the frequency of alarms, deactivating or silencing vital alarms, establishing inappropriate alarm parameters and turning down the level of alarms, all of which may affect patients’ health outcomes and threaten their lives. 10 , 13–15 Between January 2009 and June 2012, the Joint Commission on Accreditation of Healthcare Organizations received 98 alarm-related incidents; 80 of these incidents resulted in fatalities, 13 in constant function loss, and five in unexpectedly extended hospitalizations. 16 Consequently, the Joint Commission established the National Patient Safety Goals in 2014 to control and adjust the alarm safety standards.…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive amounts of clinical alarms may be the result of multiple factors. Alarm management solely through evidence-based interventions or training healthcare professionals to change their perceptions does not adequately address the high number of false alarms, alarm fatigue among healthcare professionals, and the low positive predictive value of alarm systems [ 20 ]. The risks resulting from alarms generated by various devices that are not handled promptly would be mitigated if some technical measures can be adopted, such as intelligent devices to reduce the number of false alarms, identify critical alarms, and notify healthcare professionals to respond in a timely manner.…”
Section: Introductionmentioning
confidence: 99%